Masking of midline diastema-a smokescreen approach - Yamini Rajachandrasekaran; Geeth Deepika Kottai Gandhi (Wolters Kluwer Medknow Publications, 2019)
Midline diastema is a common esthetic problem in both mixed and permanent dentition. Many innovative therapies vary from restorative procedures such as composite build-up to surgery (frenectomy), and orthodontic corrections are also available. A high frenum attachment is often the cause of persistent diastemas. Presented herewith is a case report of a 43-year-old female with a high frenal attachment that had caused spacing of the maxillary central incisors. The need for treatment in this case is mainly attributed to esthetic and psychological reasons, rather than functional ones. This case report demonstrates the removal of the abnormal labial frenum attachment through surgery and subsequent closure of maxillary diastema following prosthetic as well as restorative approach.